Implementasi E-commerce Penjualan Kaos Distro Berbasis Website pada Toko Art n Soul Purbalingga - Rizki Yanuar; Fersellia, Fersellia (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The advancement of digital technology has driven businesses to adopt e-commerce systems to enhance their competitiveness in the market. This study aims to develop a website-based e-commerce platform for Art n Soul Store in Purbalingga as a solution to declining sales and limited traditional marketing strategies. The development method used is the Waterfall model, which consists of five stages: requirements analysis, system design, implementation, testing, and maintenance. The platform is equipped with key features such as a product catalog, online payment system, and order management to improve operational efficiency and provide convenience for customers in conducting transactions. System testing was carried out using the Blackbox method, which showed that all system functions operated as expected. The result of this development is expected to help Art n Soul Store expand its market reach, improve service quality, and provide a more practical and enjoyable shopping experience for customers. With the implementation of this e-commerce platform, the store can better adapt to changes in consumer behavior, which increasingly favors online shopping.